Kontribusi Pajak Reklame Terhadap Pendapatan Asli Daerah di Kota Surabaya - Ahmad Rifaldy Nasrullah; Hendry Cahyono (Jurnal Ekonomika : INDEPENDEN, 2022)
This research to find out determine how big the impact of billing tax collection on regional income. The methods and data used are data from the Surabaya City Revenue and Financial Management Office from 2011 to 2020 using quantitative methods. The results of the study show that billboard tax collection has a positive effect on local revenue in the city of Surabaya. Keywords: local-owned source revenue, billboard tax, tax